Internal political struggle in Scotland on the issue of the region status in 2007–2011 - Kurs, Igor L. (Journal of the Belarusian State University. History, 2021)
For the first time in the national historiography, various aspects of the internal political struggle in Scotland regarding its political status in 2007–2011 are considered. The key actors in this struggle are identified, the forms and tools used by various political forces to realise their goals are highlighted, and the issue of the Scottish National Party as a government party is explored. The activity of two organisations – «National Conversation» and the Calman Commission, created at the initiative of two opposing camps of Scottish politics, is analysed. It is noted that as a result of their work, the discussion about the political future of the region was brought to a qualitatively new level, and all the main political forces in the region recognised the need to expand the powers of the Scottish Parliament.